USABILITY TESTING OF THE DIGITAL PUBLIC LIBRARY OF AMERICA WEBSITE: A CASE STUDY ON DIGITAL ARCHIVES - Maryam Az-Zahra Suharwoto; Andreas Rio Adriyanto; Maria Josef Retno Budi Wahyuni (Adisam Publisher, 2026)
User experience is part of the most important aspects to consider in developing a website. Measuring user experience would lead to creating better websites, especially websites that specialize in digital archives such as Digital Public Library of America. As one of the leading countries in digital preservation and specializing in manuscripts and historical artifacts, the Digital Public Library of America website is one of the main sources of information that people access to retrieve information regarding that subject. Large amounts of preserved manuscripts are digitalized and open to public access. Users are able to reach a wide category of historical archives through a single medium, thus allowing a larger audience as it can reach people outside of America. Through usability testing, interviews and systematic literature review, several aspects of user experience become the main highlights and key points of the Digital Public Library of America website. This study employs a qualitative methodology by gathering data through interviews, direct observations, and literature review. Its main contribution is offering a strategic framework for developing comparable websites while addressing user requirements.